2019
DOI: 10.1002/chem.201900806
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrasensitive Electrochemical Immunosensor for Nonylphenol Leachate from Instant Noodle Containers in Southeast Asia

Abstract: Nonylphenols (NPNs) are persistent endocrine disruptors and their release into the environment is causing increasing concern about their impact on human health. Herein, an ultrasensitive electrochemical immunosensor was developed for the detection of NPNs in the leachates from 61 instant noodle containers (INCs) from 8 countries across Southeast Asia. Gold nanoclusters (AuNCs) were self‐assembled with reduced graphene oxide (rGO; polyethylenimine–rGO) and used to modify a glassy carbon electrode (GCE), which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Then, the mixture was centrifuged (3000× g, 5 min), and the supernatant was discarded. The precipitate was washed three times and resuspended in DI water (0.5 mg/mL) [33].…”
Section: Preparation Of Pei-rgo-auncsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the mixture was centrifuged (3000× g, 5 min), and the supernatant was discarded. The precipitate was washed three times and resuspended in DI water (0.5 mg/mL) [33].…”
Section: Preparation Of Pei-rgo-auncsmentioning
confidence: 99%
“…For example, the experiments of Eissa et al [32] required multiple cyclic voltammetry scans to complete the modification of the sensor and the fixation of the antibody. In this study, we used self-assembly of rGO modified with polyethyleneimine (PEI) and AuNCs to obtain a composite material (PEI-rGO-AuNCs) for the surface modification of the working electrode of a set of screen-printed electrodes, which was successfully proved to detect the nonylphenols with a low detection limit [33]. The electrode surface can be modified by a simple drip coating method.…”
Section: Introductionmentioning
confidence: 99%
“…The immunosensor displays a low LOD (1.2 × 10 −11 mol L −1 ), and acceptable recoveries (84.6%–100.3%) in real sample detection. So far, widespread reports have demonstrated that label‐free electrochemical immunosensors perform well in analyzing different food safety hazards such as chloramphenicol (El‐Moghazy et al., 2018), tetracycline (El Alami El Hassani et al., 2019), Escherichia coli (Y. Huang et al., 2019; Mathelié‐Guinlet et al., 2019), nonylphenols (M. Lu et al., 2019), parathion (Mehta et al., 2016), ochratoxin A (Kunene et al., 2020; Malvano et al., 2016), and aflatoxin M1 (An et al., 2020). Apart from being labeled on antibodies, nanozymes as electrode modifiers can be used for the design of flexible label‐free immunosensing strategies for food safety hazard analysis.…”
Section: Detection Mechanisms For Analytesmentioning
confidence: 99%
“…Excess GSH-modified Au-NCs were added to the PEI-rGO solution. After 3 min of sonication and 5 min of 3000× g centrifugation, the PEI-rGO-Au-NCs was obtained by discarding the supernatants [28][29][30].…”
Section: Sensor Fabrication 231 Preparation Of Pei-rgo-au-ncsmentioning
confidence: 99%